Hot-rolled embossing of microlens arrays with antireflective nanostructures on optical glass. (6th August 2015) - Chen, Po-Lin; Hong, Rong-Hong; Yang, Sen-Yeu
Abstracts: Glass is an excellent material for optical devices requiring optical and mechanical properties better than those of a polymer. Because traditional micro- or nano-fabrication on glass substrates is typically slow and costly, the fabrication of micron- or nanometer-scale structures on glass has been a challenge. For a novel continuous fabrication of glass microlens arrays with antireflective nanostructures (AR-MLA), we have designed and implemented a hot-rolled embossing facility with synergetic heating. The mold of a hybrid micro/nanostructure was fabricated in two steps. First, a micron-scale lens cavity was embossed on a nearly pure aluminum sheet with an electroplated nickel mold; an anodic aluminum-oxide process was used to create a nanostructure on the microlens array cavity. The mold was then mounted on a roller and used in a hot embossing machine to fabricate AR-MLA on optical glass. The optical properties of the fabricated microlens with nanostructures have been verified. The image of focused spots of fabricated AR-MLA shows an effective converging ability, and the reflectance at 550 nm was decreased from 7.63 % to 0.53 % with the fabricated nanostructures. This proposed technique has proven its potential for hot-rolled embossing of glass components with micro/nanostructures.